2013
DOI: 10.1074/mcp.m112.021220
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Phosphoproteomics after Auxin-stimulated Lateral Root Induction Identifies an SNX1 Protein Phosphorylation Site Required for Growth

Abstract: Protein phosphorylation is instrumental to early signaling events. Studying system-wide phosphorylation in relation to processes under investigation requires a quantitative proteomics approach. In Arabidopsis, auxin application can induce pericycle cell divisions and lateral root formation. Initiation of lateral root formation requires transcriptional reprogramming following auxin-mediated degradation of transcriptional repressors. The immediate early signaling events prior to this derepression are virtually u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
85
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(93 citation statements)
references
References 85 publications
8
85
0
Order By: Relevance
“…Auxin might play a direct or indirect role in altering the state of chromatin and thus influence the binding of ARFs to auxin response promoters. Phosphorylation of ARF proteins (e.g., ARF2) might also influence their DNA-binding activity and phosphorylation of ARF2 may be an auxin-dependent process 24 , 25 . The study reported here along with the chromatin and phosphorylation studies summarized above suggest that it would be worthwhile to launch investigations into mechanisms involved in auxin-responsive gene expression that explore areas beyond ARF-Aux/IAA CTD interactions on promoters of auxin response genes.…”
Section: Discussionmentioning
confidence: 78%
“…Auxin might play a direct or indirect role in altering the state of chromatin and thus influence the binding of ARFs to auxin response promoters. Phosphorylation of ARF proteins (e.g., ARF2) might also influence their DNA-binding activity and phosphorylation of ARF2 may be an auxin-dependent process 24 , 25 . The study reported here along with the chromatin and phosphorylation studies summarized above suggest that it would be worthwhile to launch investigations into mechanisms involved in auxin-responsive gene expression that explore areas beyond ARF-Aux/IAA CTD interactions on promoters of auxin response genes.…”
Section: Discussionmentioning
confidence: 78%
“…However, the way by which FRO2 is regulated is not yet clear. FRO2 is modified by Ser phosphorylation at three sites (Zhang et al, 2013) and by Met oxidation at two sites (Engelsberger and Schulze, 2012). It remains to be determined if any of those modifications have a regulatory function that is sensitive to Mn.…”
Section: Mtp8 Allows Chlorosis-free Growth By Preventing Mn From Inhimentioning
confidence: 99%
“…Moreover, none of these resources provide simultaneous quantification of unphosphorylated and phosphorylated forms of a protein. Such parallel comparisons are essential to distinguish changes in the phosphorylation state of a particular protein from changes in the overall abundance of that protein, as illustrated by studies in plants (Reiland et al, 2011;Zhang et al, 2013) and other systems (Rigbolt et al, 2011). Until very recently, comprehensive coverage of the proteome was not possible; therefore, the likelihood of identifying the same protein in both a phosphoproteomic and proteomic analysis was low, making such parallel comparisons difficult.…”
Section: Introductionmentioning
confidence: 99%